Revitalisasi Peran Komite Sekolah dalam Perumusan Kebijakan Pendidikan di SMP PGRI Kambu Nusa Tenggara Barat - Muhammad Zulfahmi Akbar (Yayasan Madinah Al-Aziziyah, 2026)
The role of school committees in formulating participatory and adaptive education policies remains marginal and is often limited to administrative functions. This study aims to explore and revitalize the strategic role of school committees in decision-making processes, particularly at the secondary school level. Using a qualitative case study approach, data were collected through participant observation and semi-structured interviews involving principals, senior teachers, and school committee members. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The study findings indicate that although school committees are partially involved in planning activities such as budgeting, extracurricular programs, and student admission policies, their involvement in strategic aspects such as curriculum reform and long-term policies remains very limited. This study recommends the need for systematic training on education policy and school governance, the development of practical standard operating procedures (SOPs), and democratic restructuring of committees to ensure institutional independence. Strengthening in these areas will enable school committees to act as effective partners in realizing transparent, accountable, and high-quality education governance.